(untitled) (Heritage, 2024)
The stability of the course of internal and foreign policy directly depends on internal, regional and even global security. Establishing a clear foreign policy direction requires long-term/strategic partnerships, certain and positive security-political opportunities in the environment, which is especially difficult in the dynamic geopolitical environment such as Eastern Europe. Frequent changes in the foreign policy directions of Eastern European countries are the result of conflicts between mutually exclusive geostrategic interests and pretensions in different historical-political contexts, which often led to crisis and even conflict moments. Unfavorable security conditions in Eastern Europe caused by the current conflict in Ukraine fueled a security dilemma, the effects of which were soon felt in all social spheres. Bearing that in mind, the subject of this paper is the research and critical analysis of the security dilemma as a factor of foreign policy action in the context of the Ukrainian conflict, which includes both long-term (strategic) and short-term directions, as well as regional and global political goals of the countries of Eastern Europe. The countries of Eastern Europe that are direct participants in the Ukrainian conflict were excluded: the Russian Federation and Ukraine, and the focus was on the evaluation of the foreign policy directions of action of the countries of the mentioned region. All analyzed energetic, geographical, demographic, economic and political-security features of Eastern Europe are a suitable basis and, directly or indirectly, affect the realization of certain security-threatening phenomena, among which are certainly the most dangerous military threats, which have the potential to spread and intensify. The reactivation of the security and defense dilemma, which was actualized after the military intervention of the Russian Federation in Ukraine, put the countries of Eastern Europe under the microscope and put their external political direction to the test. However, it is clear that the countries of this region do not have absolutely mutually compatible foreign policy goals and interests in those areas where it is necessary to protect their national values. While the majority inconsistent countries decide to prioritize their own national security, the majority consistent countries, by helping Ukraine, actively participate in maintaining and strengthening the regional security dilemma.